Tinjauan Pemasangan Road Barrier terhadap Kepatuhan Pengemudi dalam Berlalu Lintas di Persimpangan Kota Medan - Suryaningsih Silalahi (CV Rewang Rencang, 2025)
This study aims to evaluate the effectiveness of the road barrier installation policy in improving driver compliance and reducing traffic violations in Medan City, particularly at the William Iskandar and Putri Merak Jingga intersections. Furthermore, the study seeks to identify the factors influencing the successful implementation of this policy from the perspectives of drivers, local residents, officers from the Department of Transportation, and members of the Traffic Police (Satlantas). The research employed a qualitative approach using a descriptive study design. Data were collected through in-depth interviews with drivers, street vendors around the intersections, Department of Transportation officers, and Traffic Police officers on duty, complemented by direct observation and field documentation. Data analysis was conducted through a process of reduction, presentation, and inductive conclusion drawing to obtain a comprehensive understanding of the policy’s effectiveness. The findings indicate that the installation of road barriers in Medan City has proven to be quite effective in improving order and driver compliance with traffic regulations. Following the implementation of this policy, the rate of traffic violations decreased from approximately 65% to 25–30%, demonstrating a positive behavioral change among road users. From the perspective of the Traffic Police, the presence of road barriers helps reduce potential violations in vulnerable areas and facilitates traffic monitoring, although certain locations still require adjustment to prevent vehicle congestion.